Do teachers' achievement goals and self-efficacy beliefs matter for students' learning experiences? Evidence from two studies on perceived teaching quality and emotional experiences. (December 2021) - Daumiller, Martin; Janke, Stefan; Hein, Julia; Rinas, Raven; Dickhäuser, Oliver; Dresel, Markus
Abstract: Although teacher motivation is posited to matter for students' learning experiences, this remains largely uninvestigated, particularly in higher education. In two studies, we analyzed the role of higher education teachers' achievement goals and self-efficacy for students' learning experiences. In Study 1 ( k = 166 teachers, n = 2, 106 students), we assessed teachers' motivations at the semester start, and students' course-specific perceptions of teaching quality (overall rating, learning) and emotions (joy, boredom) at the semester end. Latent multilevel modeling indicated favorable associations for teachers' self-efficacy, but not for their goals. In Study 2 ( k = 96 teachers, n = 16, 009 students), we assessed the same constructs and measured students' learning experiences weekly regarding 828 specific course sessions. Additionally, we included teachers' session-specific motivations. Results replicated the effects of self-efficacy on the teacher-level and suggested that performance-approach and performance-avoidance goals primarily matter on the level of specific sessions. This affirms the relevance of teacher motivations and illuminates the importance of their specificity. Highlights: With two studies, we test whether and how teacher motivations matter for students. We combined teacher and student data and included session-specific motivations. Teachers' general self-efficacy positively predicted students' learning experiences. Achievement goals primarily mattered on the level of specific course sessions. Overall, this illuminates the importance of the specificity of teacher motivations.